Meanings and Functions of Money in Different Cultural Milieus. [article]. - Cohen, Dov
We explore the psychological meanings of money that parallel its economic functions. We explore money's ability to ascribe value, give autonomy, and provide security for the future, and we show how each of these functions may play out differently in different cultural milieus. In particular, we explore the meanings and uses of money across ethnic groups and at different positions on the socioeconomic ladder, highlighting changes over the last 50 years. We examine the dynamics of redistribution between the individual, the family, and the state in different cultures, and we analyze the gendering of money in the world of high finance and in contexts of economic need. The field of behavioral economics has illustrated how human psychology complicates the process of moving from normative to descriptive models of human behavior; such complexity increases as we incorporate the great diversity within human psychology. -- (from the author)